Human Immunodeficiency Virus Acquisition Associated with Genital Ulcer Disease and Herpes Simplex Virus Type 2 Infection: A Nested Case-Control Study in Rakai, Uganda - Serwadda, David; Gray, Ronald H.; Sewankambo, Nelson K.; Wabwire-Mangen, Fred; Cheng, Michael Z.; Quinn, Thomas C.; Lutalo, Tom; Kiwanuka, Noah; Kigozi, Godfrey; Nalugoda, Fred; Meehan, Mary P.; Morrow, Rhoda A.; et al. (The Journal of infectious diseases, 2003)
To assess the timing of symptomatic genital ulcer disease (GUD) relative to human immunodeficiency virus (HIV) seroconversion, we studied 248 case subjects who underwent HIV seroconversion and 496 HIV-negative control subjects, at 3 interview visits conducted at 10-month intervals: visit 1, before HIV acquisition; visit 2, after seroconversion; and visit 3, 10 months after detection of seroconversion. Odds ratios (ORs) and 95% confidence intervals (CIs), for HIV acquisition, were estimated by logistic regression. HIV load was measured by RNA–polymerase chain reaction, and herpes simplex virus type 2 (HSV-2) serologic testing used HerpeSelect EIA with Western blot confirmation. The OR of HSV-2 seropositivity associated with HIV acquisition was 1.7 (95% CI, 1.2–2.4). Prevalence of GUD was increased among case subjects, at visits 2 (OR, 3.2; 95% CI, 1.9– 5.3) and 3 (OR, 2.1; 95% CI, 1.1–3.9). HIV load was increased in HSV-2–seropositive case subjects, compared with that in HSV-2–seronegative subjects, at 5 (Pp.04) and 15 (Pp.02) months after seroconversion. HIV acquisition is associated with HSV-2 seropositivity, and GUD is increased after seroconversion. HIV load is increased in HSV-2–positive subjects who seroconverted, suggesting a role for treatment of HSV-2 infection in HSV-2–seropositive, dually infected individuals.
Keywords: HIV acquisition; seroconversion; Genital Ulcer Disease